Comparative Efficacy of New Interfaces for Intra-procedural Imaging Review: the Microsoft Kinect, Hillcrest Labs Loop Pointer, and the Apple iPad. - Chao, Cherng; Tan, Justin; Castillo, Edward; Zawaideh, Mazen; Roberts, Anne; Kinney, Thomas (Journal of Digital Imaging, 2014)
We adapted and evaluated the Microsoft Kinect (touchless interface), Hillcrest Labs Loop Pointer (gyroscopic mouse), and the Apple iPad (multi-touch tablet) for intra-procedural imaging review efficacy in a simulation using MIM Software DICOM viewers. Using each device, 29 radiologists executed five basic interactions to complete the overall task of measuring an 8.1-cm hepatic lesion: scroll, window, zoom, pan, and measure. For each interaction, participants assessed the devices on a 3-point subjective scale (3 = highest usability score). The five individual scores were summed to calculate a subjective composite usability score (max 15 points). Overall task time to completion was recorded. Each user also assessed each device for its potential to jeopardize a sterile field. The composite usability scores were as follows: Kinect 9.9 (out of 15.0; SD = 2.8), Loop Pointer 12.9 (SD = 13.5), and iPad 13.5 (SD = 1.8). Mean task completion times were as follows: Kinect 156.7 s (SD = 86.5), Loop Pointer 51.5 s (SD = 30.6), and iPad 41.1 s (SD = 25.3). The mean hepatic lesion measurements were as follows: Kinect was 7.3 cm (SD = 0.9), Loop Pointer 7.8 cm (SD = 1.1), and iPad 8.2 cm (SD = 1.2). The mean deviations from true hepatic lesion measurement were as follows: Kinect 1.0 cm and for both the Loop Pointer and iPad, 0.9 cm (SD = 0.7). The Kinect had the least and iPad had the most subjective concern for compromising the sterile field. A new intra-operative imaging review interface may be near. Most surveyed foresee these devices as useful in procedures, and most do not anticipate problems with a sterile field. An ideal device would combine iPad's usability and accuracy with the Kinect's touchless aspect.